Could increasing dividends predict asset valuations in the Brazilian electricity sector? - da Silva, Alexandre Rodrigues; Kirch, Guilherme (Revista UNEMAT de Contabilidade, 2022)
According to Wang (2004), the stock markets have different behaviors in the short and long term. Dividend investment sees fewer years with losses, adding significant utility to the investor (CLEMENS, 2012). The purpose of this study is to demonstrate whether the payment of dividends can relate to the future gain in value of their respective shares in companies in the Brazilian electricity sector. Results: the findings showed a positive variation in the value of assets one year after their acquisition in that group that had a positive change in dividends in the previous year, compatible with the “Dogs of Dow” strategy, and this relationship was not found for longer periods of time, both for dividends and for stocks prices. Thus, it is suggested that the strategy of seeking asset valuation based on its previous dividend payment should be limited to the previous year's dividend payment period, aiming at a horizon of one year after the purchase of the respective company's share.